Biopetrol synthesized from rubber seed oil by zeolite catalyst :effect of ethanol in solvent extraction of rubber seeds - Pillai Ganasekaram, Regupathi Raja (2012)
Currently, most of the bio-petrol is produced from the refined or edible type oils such as the utilization of palm oil for the production of more environmental friendly biofuels.However,by extracting rubber seed oil(RSO)from the rubber seeds,this method is more favorable as the RSO contains more fatty acid to be produced into bio-petrol. The rubber seeds are readily available,cheap and help to improve the socioeconomic issues.The RSO is extracted using the Soxhlet Extraction method.The cleaned,shelled and milled rubber seeds are placed into a thimble in the main chamber of the extractor.The solvent ethanol in the receiving flask is left to boil until it vaporizes and condensed,filling up the main chamber,extracting the RSO from the rubber seeds. The catalytic cracking of the mixture of 0.1L of RSO,20g of catalyst and bumping chips at 300 0C for 45 minutes using Zeolite catalyst is to boost up the rate of reaction so that more successful reactions between the reactant particles can occur.The presence of Isooctane in a sample detected using Gas Chromatogram indicating that bio-petrol can be produced. Standards of different ratio mixtures of hexane and Isooctane were used to obtain chromatograms for Isooctane until a calibration curve is plotted from which the Isooctane produced can be determined.The results show that the actual concentration of Isooctane is very big.This could be explained using the cause of interlayer spacing of catalyst structure,larger surface area for reactions to occur,various types of fatty acid mixture present in RSO,the incorrect chromatogram modifications and the contamination in RSO.The mass of catalyst and volume of RSO used will affect the percentage of concentration of Isooctane in samples.As a conclusion, Bio-petrol can be produced from RSO using Zeolite catalyst in the catalytic cracking process.